The attentive brain - Parasuraman, R. (A Bradford book, 1998)
Of the myriad tasks that the brain has to perform, perhaps none is as crucial to the performance of other tasks as attention. A central thesis of this book on the cognitive neuroscience of attention is that attention is not a single entity, but a finite set of brain processes that interact mutually and with other brain processes in the performance of perceptual, cognitive, and motor skills.